Ductile cooling phase change material. Issue 9 (13th August 2020) - Gogoi, Pratahdeep; Li, Zheng; Guo, Zipeng; Khuje, Saurabh; An, Lu; Hu, Yong; Chang, Shuquan; Zhou, Chi; Ren, Shenqiang
Abstract : The as-manufactured elastic and flexible hydrogels demonstrate a potential application in the ductile cooling phase-change medium. Abstract : Cooling represents a considerable fraction of energy consumption. However, it is indispensable to develop eco-friendly, biocompatible, and ductile cooling materials for personal applications. In this study, we demonstrate the ductile cooling ability with phase change of thermally passivated hydrogel composite materials with additive manufacturing ability. Thermal evaluation of such water-based composites indicates a superior cold retention capacity with a cooling comfort over 6 hours, while the composite displays a full recovery when strained up to 80% in uniaxial compression tests as a result of the intertwining between covalent and ionic bonds. A three-layered rectangular model was utilized to simulate the problem in a steady-state thermal analysis to study the cooling effect. Our findings indicate the potential of hydrogel as a cooling phase-change medium and its contribution towards ductile cooling applications.